Quinta da Boavista - Da Memória à Intervenção - João Luís de Pereira Dias e Tenedório Fânzeres (2015)
The object of study of the present dissertation is the ruin of a traditional farmhouse of the Alto Minho Region and its surroundings. The choice of this theme emerges from the issues that will be raised during the architectural design exercise and to find answers to these same questions, ultimately serving as a "laboratory" for research and design of a proposal for an eventual intervention. This process aims to ensure the transformation and adaption of the site without losing its "genius loci", which reflects the character of the place and should remain practically unchanged, and when subject to change, address to the history of the past. It is crucial to understand how the new architecture intervention will transform the preexistent, what clues will it imbibe from the place, what the approach to take, which references to use, how to build the adopted solutions and how it accepts or challenges the tradition. The ruins have always inspired mixed feelings. In addition to its sentimental and documental value, the ruin also holds didactic relevance, in the sense that it conveys a message, a conceptual, technical and formal inheritance. Piece of architecture eroded by the time, architectural fragment of the past, phenomenon that has gone through different stages of the history, it provides clues about the place, the ways of living, construction techniques, dwelling problems and spatial materiality. Therefore, the ruin transmits knowledge, manifests continuity and identifies distance (time), transforming itself in operative and relevant material for the architect. This patrimonial heritage provides both insight and also constitutes a "resource" in itself. It is intended to tune the architect to the intervention on the ruin, since the interest of the architect in learning from the examples of the past, and in this case in particular, more than the usual curiosity, arises from an operative determination that seeks the importance of the "how", "why", "for whom", not exempting drawing, our main instrument of analysis and work, to do so. There is, in this specific situation, the need to promote a topographic restoration, a interpretation of historical data, in order to "(re)compose" and understand volumetric positioning options, occupation and growth of the surrounding area, in relation to the study case. This dissertation comes as response to a desire of analysis, by turning the design process into architectural discussion content. It is intended to raise questions resulting from a critic positioning on the development of this experience, considering the acquired knowledge from this architectural project with a real context and specifications.